Idealized Design: How to Dissolve Tomorrow's Crisis...Today - Russell L. Ackoff; Jason Magidson; Herbert J. Addison (Upper Saddle River Wharton School Pub., 2006)
What's the best way to drive fundamental, transformative change within your organization? Envision your ideal solution: then, work backwards to where you are. It's called idealized design, and -- as executives in hundreds of organizations will testify -- it's one of the most powerful techniques you'll ever use. Authored by its legendary creator, Wharton Professor Emeritus Russell Ackoff, and leading practitioner Jason Magidson, Idealized Design covers every facet of this breakthrough methodology. You'll learn the fundamental differences between idealized design and traditional process re-engineering, and understand how idealized design eliminates many conventional obstacles to change. Start-to-finish techniques and examples drawn from hundreds of companies, non-profits, and government organizations will show you how to use idealized design to solve your own crisis of tomorrow...today.
Age Group: Adult
The stages of idealized design -- Organizing the process -- Preparing for an idealized design process -- Business enterprises -- Not-for-profit and government organizations -- Process improvement -- Problem dissolving -- Facilities and sites design -- Take the plunge -- The urban challenge -- The health-care challenge -- The challenge to government -- Energetics (business enterprise) -- Academy of Vocal Arts (not-for-profit) -- White House Communications Agency (government).
Includes bibliographical references (p. 267-275).
Keywords: Business; Management; Leadership; Design; Creative thinking; Technological innovations; Organizational effectiveness; Corporate culture